2023
DOI: 10.1097/aog.0000000000005192
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives Regarding Clinician Communication During Telemedicine Compared With In-Clinic Abortion

Abstract: Telemedicine appears to be a beneficial, patient-centered approach to critically needed first-trimester abortion services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“… 26 This problem does not, however, appear to be confined to remotely supported medical abortion: other research has shown that patients who received medication abortion through telemedicine ranked their communication with the clinicians more favourably than did those in traditional, in-clinic settings. 44 …”
Section: Discussionmentioning
confidence: 99%
“… 26 This problem does not, however, appear to be confined to remotely supported medical abortion: other research has shown that patients who received medication abortion through telemedicine ranked their communication with the clinicians more favourably than did those in traditional, in-clinic settings. 44 …”
Section: Discussionmentioning
confidence: 99%